Alvin York : A New Biography of the Hero of the Argonne - Mastriano, Douglas V. (Book collections on Project MUSE., 2014)
Alvin C. York (1887--1964) -- devout Christian, conscientious objector, and reluctant hero of World War I -- is one of America's most famous and celebrated soldiers. Known to generations through Gary Cooper's Academy Award-winning portrayal in the 1941 film Sergeant York, York is credited with the capture of 132 German soldiers on October 8, 1918, in the Meuse-Argonne region of France -- a deed for which he was awarded the Congressional Medal of Honor. At war's end, the media glorified York's bravery but some members of the German military and a soldier from his own unit cast aspersions on his.